Comparison of Birth Weights of Pre-Delivery Anemic and Non-Anemic Routine Iron Supplemented Pregnant Women - Tolga Atakul (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the effects of pre-delivery hematological parameters on birth weight and to compare their relationship with maternal age and parity in women who had taken routine iron supplementation during pregnancy